Topical Laporteadecumana Leaves Extract Could Increase IL-6 Levels and PG-E2 Levels among Women in Active Phase of the First Stage of Labor - HL, Sisma (International Journal of Psychosocial Rehabilitation, 2020)
The study aims to explain the effect of Laporteadecumana (LD) on IL-6 levels and PG-E2 levels among women in active phase of the first stage of labor. The mean age of respondents was 23-26 years, most from the ethnic group of 70%. They had an occupation as housewives of 92.5%, and given birth more than once of 67.5%. There were no significant differences (p-value > 0.05). The characteristics could be controlled and did not have a biased effect on the results. There was an increase in IL-6 levels and PG-E2 levels after treatment. The variable of IL-6 levels, the sequence of the increase in IL-6 levels from the highest value was SP+V (18.34 ± 22.26), LD+SP (16.21 ± 23.12), LD+KS (12.81 ± 20.56) and the lowest increase was in KS+V (5.76 ± 6.59). Overall given treatment to all groups did not affect IL-6 levels (p=0.541). The highestdifference in mean increase was in the SP+V group (802.50 ± 444.16) and the lowestwas in the LD+SP group (491.90 ± 475.25). Overall given treatment to all groups did not affect PG-E2 levels (p=0.623). L. decumanacould increase the levels of IL-6 and PG-E2according to the labor progress.